Self-Regulated Writing of English Learners: Intervention Development - Akhmedjanova, Diana; Moeyaert, Mariola (Frontiers in Education, 2022)
The goal of this study was to develop and test an intervention in order to improve academic writing and SRL skills of English learners (ELs). ELs are well-represented across university and college campuses in the U. S. While most of them thrive academically and receive their undergraduate and graduate degrees, a majority of ELs experience difficulties with academic writing such as limited English proficiency levels and opportunities to practice academic writing. Therefore, there is a need to develop and examine evidence-based interventions to promote the development of academic writing skills of ELs. One promising line of research involves adding instruction in self-regulated learning (SRL) to writing courses. In this study, the SRL writing intervention was delivered as a one-credit semester-long course taught at a medium research university. A mixed-methods research design, combining single case quasi-experimental design to collect quantitative data and focus group interviews to collect qualitative data, was used with undergraduate ELs (n=8) from Southeast Asia. The results of this study revealed that the SRL writing intervention had a small positive effect on the quality of students’ persuasive writing skills, but no effect on students’ SRL skills. Focus group interviews suggested that students appreciated learning about SRL skills, but found the SRL journal confusing and frequent. These findings suggest that both writing and SRL skills are teachable, but may require more time and adjustments to the teaching and learning methods employed in the study. Recommendations for the development of the improved intervention are also provided.